Factors Affecting the Spatial Distribution of Oviposition Sites for Tandem Black Saddlebags Dragonflies (Odonata: Libellulidae). Issue 1 (5th May 2015) - Thornton, Jessica L.; Switzer, Paul V.
Abstract : Oviposition site location may be affected by (1) factors influencing the costs and benefits to the offspring (e.g., resource availability, competition, predation risk) and (2) factors influencing the costs and benefits to the female (e.g., predation risk or mate harassment). In cases in which both the male and female are involved in locating a site, costs and benefits may differ for each parent and the resulting oviposition site location may represent the outcome of selection pressures on one or both of them. We studied oviposition behavior in the black saddlebags dragonfly ( Tramea lacerata Hagen), a species in which the male and female typically remain together (i.e., in tandem) while traveling among potential oviposition locations. Oviposition sites tended to be away from pond shoreline at the outer edge of the vegetation on the water's surface. We found that tandems distributed their oviposition locations widely around the pond, and interactions with other dragonflies (typically other T. lacerata, either territorial males or tandems) led to a larger distance between consecutive oviposition locations. Interestingly, for 10% of the tandems, the female became separated from the male and oviposited solitarily multiple times. These solitary females spent significantly less time and traveled significantly smaller distances between successive oviposition sites than when in tandem. Our results indicate that while some aspects of oviposition behavior and site selection may be consistent between the male and female (e.g., the characteristics that make a site suitable), other aspects, such as the distribution of sites, may be a result of a differing benefits and costs for the two sexes, perhaps as a consequence of potential sperm competition.